To solve the equation \( \frac{y - 1}{-11} = -3 \), let's go step by step and fill in the missing terms and select the missing descriptions.
-
Start with the given equation: \[ \frac{y - 1}{-11} = -3 \]
-
Multiply both sides by -11 (to eliminate the fraction): \[ y - 1 = 33 \]
-
Now, we need to isolate \( y \). Add 1 to both sides: \[ y = 33 + 1 \]
-
Simplifying gives us: \[ y = 34 \]
So the complete process is:
- Fill in the missing term: \( \text{Multiply both sides by -11} \)
- Select the missing description: \( \text{Add 1 to both sides} \)
Final answer: \[ y = 34 \]